(untitled) (Research, Society and Development, 2021)
The search for alternative, renewable, clean and sustainable energy sources is urgent in contemporary civilization and an area of intense scientific and technological research. The teaching of Science, in particular Physics, is urged to contribute by offering theoretical and conceptual subsidies to students, so that they can understand, reflect and participate in the debate on the subject as citizens. As a contribution to this educational demand, a mobile device application was developed for didactic purposes that simulates the operation of a photovoltaic solar energy system based effectively on technical parameters of the current state of the art. As a result, we obtained an application with a simple, flexible and intuitive interface, capable of addressing the didactic requirements of remote and face-to-face classes in any high school grade. The creation of the application is aligned with contemporary technological trends of ubiquity and mobility of potential learning resources in society, intensely connected by digital communication technologies and constitutes a viable alternative for teaching topics related to the use of photovoltaic solar energy capable of contribute to teaching and reflections about the contemporary energy matrix.